Mir-193a-5p Replacement Can Alter Metastasis Gene Expression in Breast Adenocarcinoma Cells In Vitro - Monireh Khordadmehr; Roya Shahbazi; Behzad Baradaran; Sanam Sadreddini; Dariush Shanehbandi; Khalil Hajiasgharzadeh; Masoumeh Firouzamandi (Tabriz University of Medical Sciences, 2020)
Background: Recent evidence presented the significant role of the microRNA-193 (miR-193) family in biological processes by the contribution of specific targeting, which mainly display as a tumor suppressor in various cancers. In the present study, we evaluated the effect of miR-193a-5p replacement on some metastasis gene expression in metastatic breast cancer (BC) cells. Methods: For this purpose, firstly, the quantitative real-time polymerase chain reaction (qRTPCR) was used to detect the miR-193a-5p expression in the MDA-MB-231 BC cell line. Subsequently, miR-193a-5p was transfected into the cells, and the expression levels of ROCK1 (Rho‑associated, coiled‑coil containing protein kinase 1), CXCR4 (Chemokine Receptor-4), CD44, and vimentin genes were evaluated by qRT-PCR. Results: The expression level of miR-193a-5p strongly reduced in MDA-MB-231 cells. Interestingly, the ROCK1 (P < 0. 001), CD44 (P < 0.0001), CXCR4 (P < 0. 001) and vimentin (P < 0. 001) expression levels significantly decreased following miR-193a-5p transfection in MDA-MB-231 BC cells. Conclusion: To conclude, it seems that miR-193a-5p restoration can attenuate the metastatic behavior of BC cells in vitro through decreased expression level of metastasis-related genes and may constitute an effective novel therapeutic strategy in miRNA-replacement therapy and treatment of metastatic breast adenocarcinoma in the future.